Prevalence of common oral health problems among school going children aged 12-15 years in a rural block of Haryana: a cross-sectional study - Ankesh Poonia; Seema Sharma; Anoop Grover; Annu Yadav; Akshay Kumar; Nikhil Sheoran (International Journal Of Community Medicine And Public Health, 2026)
Background: Oral diseases among children are a significant public health problem as it can affect the physical, mental and social dimensions of the individual. It can adversely affect the attendance and performance of the child in schools and attendance of the parent in the workplace as well. To estimate the prevalence of oral health problems among school going children aged 12-15 years in a rural block of Haryana. Methods: A school based cross-sectional study was conducted in government middle and high school. A pre-designed and pre-tested proforma was used for collecting the information. Oral examination was carried out under daylight using a mouth mirror, oral probe and torch (when required), with the child in a sitting position within the school premises in the presence of school authorities. Data was analyzed by using percentages. Results: Dental caries (48%) emerged as the most common condition, followed by deposits on tooth (46.1%) and fluorosis (43.6%). Other conditions included dental aches (13.8%), foul smell (10.8%), interdental spacing (4.7%), retained deciduous teeth (2.7%), fractured teeth (2.2%), tongue problems (1.6%) and gum problems (0.8%). Conclusions: The overall pattern indicates a substantial burden of preventable oral conditions among school going adolescents.